Speech Acts In Arabic Poetry A Pragmatic Approach - Amneh Hussein Mohammad AlRamadneh (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The main objective of this study was to examine the use of speech acts theory in analyzing Arabic text literature, specifically, Al-Faisal's poetry, to gain a deeper understanding of the speaker's meaning and the beauty of language usage. The study employed speech acts theory, a branch of pragmatics that focuses on how language is utilized to impart information and carry out actions such as making promises, requests, and giving orders. Despite some criticism and questions surrounding the theory, its significance in analyzing text and understanding the speaker's intention and effect on the audience cannot be denied. The research results showed that Al-Faisal's poetry is rich in expressive value and is characterized by linguistic richness and artistic creativity. However, the study concluded that there are creative expressive forms in the Arabic language that do not fit into Searle's classification of illocutionary acts due to their performative nature with double meanings. As a result, the study recommends increasing applied studies on the Arabic text to uncover these expressive forms and enhance our understanding of the language.